2012
DOI: 10.1007/s12350-012-9571-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of rest and post-stress left ventricular volumes and left ventricular ejection fraction on gated myocardial perfusion imaging (MPI) and echocardiography in patients with transient ischaemic dilation on adenosine MPI: Myocardial stunning or subendocardial hypoperfusion?

Abstract: Transient dilation of the left ventricle on adenosine MPI is not related to chamber enlargement and myocardial stunning, but is more likely a function of subendocardial hypoperfusion and impaired coronary flow reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…35 This supports the present unexpected results regarding both TID ratio and SWMS in the SDI protocol with vasodilator stress. Moreover, if physicians did not need TID ratio or changes of wall motion between stress and rest scan in clinical reading, the second acquisition might not be necessary.…”
Section: Discussionsupporting
confidence: 91%
“…35 This supports the present unexpected results regarding both TID ratio and SWMS in the SDI protocol with vasodilator stress. Moreover, if physicians did not need TID ratio or changes of wall motion between stress and rest scan in clinical reading, the second acquisition might not be necessary.…”
Section: Discussionsupporting
confidence: 91%
“…While myocardial perfusion can not be directly evaluated by ECHO or invasive CAG, nuclear cardiac imaging tests provide simultaneous assessment of myocardial perfusion and LV function (24,27). So, defining true myocardial ischemia on the basis of transient regional wall motion abnormalities related to ischemic LV dysfunction is possible (28,29). The good agreement between stress ECHO and gated MPS studies has been reported regarding segmental wall motion analysis (25).…”
Section: Discussionmentioning
confidence: 99%
“…This rare occurrence is likely to also manifest through other markers of poor prognosis such as high percentage of ischemic myocardium on imaging, transient ischemic dilatation, and low poststress ejection fraction. 21,22 Indeed, these strong predictors of risk may reduce the prognostic power of vasodilatorinduced hypotension on multivariate analysis as suggested by the findings of Witbrodt et al 8 Further, since the majority of patients will experience a drop in BP with vasodilator stress due to direct peripheral vasodilation, it becomes difficult if not impossible to distinguish those who experience a drop of BP due to ischemia from the normal response. In contrast, an abnormal heart rate response to vasodilator stress, i.e., a blunted response, runs directionally opposite to the normal response seen in the majority of patients, a brisk increase in heart rate.…”
Section: Blood Pressure Response To Vasodilator Stressmentioning
confidence: 99%